Randomized Controlled Trial on Mind-refreshing and Orifice-opening Needling Method and Cerebral Infarction - 杨志新 卞金玲 许军峰 申鹏飞 熊杰 郭家奎 张智龙 李军 石学敏 (Journal of acupuncture and tuina science, 2008)
Objective To observe the clinical effect of treating remission-stage cerebral infarction with mind-refreshing and orifice-opening needling method. Method Six hundred cases of cerebral infraction were randomized on the basis of disease phase. The 234 cases in remission stage were randomized into treatment group (116 cases) and control group (118 cases). Besides routine Western therapies, the cases in the treatment group were combined mind-refreshing and orifice-opening needling method and the cases in the control group were combined with conventional needling method. The treatment was done once every day for 4 weeks. The follow-up was done for six months. Result The baseline material in the two groups has good compatibility ( P >0.05) and the treatment group is better than the control group ( P <0.05). Conclusion The mind-refreshing and orifice-opening method is safe and act to improve symptoms of patients during remission stage, reduce disability, prevent disease progression and improve quality of life.